TGfU – Would you know it if you saw it? Benchmarks from the tacit knowledge of the founders. (November 2014) - Butler, Joy
This paper explores the tacit expert knowledge and understanding about games curriculum and pedagogy of three men, Len Almond, David Bunker, and Rod Thorpe, credited as the founders of the Teaching Games for Understanding (TGfU) model. The model emerged from teacher practice in the late 1970s and was little theorized at the time, apart from a handful of articles written by the founders. This paper attempts to retrospectively theorize and represent the founders' ideas in terms of the beliefs, intentions, and actions they believed to be fundamental to TGfU. From here, some benchmarks are proposed so that TGfU can be more easily recognized when it is being practised and researched. Data were collected through two online sequential questionnaires, informal personal telephone interviews, and emails. All data were member checked throughout the two-year study. Both of the questionnaires were completed by the three founders in the persona of their 'ideal' TGfU teacher, in the hope that this would lead to greater clarity of response. The first questionnaire, called the Teaching Perspectives Inventory (TPI), was developed by Daniel Pratt and builds a profile of teacher beliefs, intentions, and actions, which are then grouped into five perspectives and ranked by personal bias. Questions posed on SurveyGizmo formed the second questionnaire, which helped the founders reflect further about their ideal teacher's beliefs, intentions, and actions, as they became apparent in the dominant and recessive perspectives identified in the TPI profiles. The findings were grouped into the founders' beliefs and intentions about: (1) learners and learning; (2) content; and (3) teachers' role and responsibilities. The data forming what the founders' considered to be best pedagogical practice formed eight areas for consideration to include: (1) preparation; (2) management; (3) starting a TGfU lesson; (4) continuing a TGfU lesson; (5) teacher behaviours; teacher focus during a game; (7) teacher expectations; and (8) learning environment. This paper aims to provide a starting point for further research, debate, and reflection as we engage with the founders' intentions – to provide students with teaching that is an overt social, cultural, and relational activity, as well as a set of plans, practices, and actions.